Tourism potential of the territory in regional economic development - Horb, Kostiantyn (Human Geography Journal, 2016)
The concept of tourism’s potential of the territory is analyzed in this article; the concept of tourism development in the region is grounded and its overall scheme is built. The tourist potential of the territory as a base of regional tourism development is a complex system which consists of geographical «core» and «add» of other factors and conditions which promote such development. At the same time, the core of tourism’s potential in one’s turn, is considered at two levels: the first (lower) level provides a set of identified and prepared tourism resources for use and expanded tourism infrastructure which is reinforced by institutional support for tourism development. The second (top) level is a set of tourist destinations, tourist clusters, tourist landscapes and regional tourism product. In particular these innovative forms of tourism territorial units in their connection are the key indicators of regional tourism development and they should be the main object of attention of the regional administration and other entities of the regional economy which are interested in tourism development. Transit and trans-regional tourist destinations (TD) deserve special attention and generally promote a positive image of a tourist area but not always ensure the economic success of the regional tourism. In this connection, regional authorities, representatives of tourism business and the public should not just study the demand and promote their TD among foreign tourists but accordingly to take care about their inclusion in the tourist routes which are developed and sold by tour operators in other regions and countries. Subjects who promote destinations of the region on the tourism market should also promote not only places of tourist interest as such, but its tourist facilities and their services and in generally help to increase the duration of visiting of the region.